How Does AI Handle Uncertainty in Clinical Decision Making? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2016)
Uncertainty is an inherent and unavoidable aspect of clinical medicine. From ambiguous patient histories to the probabilistic nature of diagnostic tests and ...
Keywords: AI in Clinical Decision Support; Handle; Uncertainty; Clinical; Artificial Intelligence; Machine Learning; Deep Learning